Effect of microneedling by dermaroller on acne scars: an observational study at tertiary care hospital - M. Momin, Anjum; B. Vaishnani, Jignesh; S. Bosamiya, Sanjay; A. Mistry, Ankita (International Journal of Research in Medical Sciences, 2023)
Background: Post acne facial scar is very distressing phenomenon. There are many treatment options like laser resurfacing, dermabrasion, microdermabrasion and non-ablative laser resurfacing but it may cause adverse effects and interference with the daily activities of the patient. Microneedling or dermaroller therapy is newer modality in management of acne scars with satisfactory improvement and no significant side effect. Objective of our study was to evaluate efficacy and safety of microneedling in the treatment of atrophic facial acne scars. Methods: Twenty-eight patients of Fitzpatrick skin type IV to V having atrophic facial acne scars and fulfilling inclusion criteria were treated with multiple sittings of microneedling (dermaroller) treatment at monthly interval. Goodman and Baron’s qualitative and quantitative acne scar grading system was used for assessment. Patients were evaluated clinically and by serial photography. Presence of any active infection, active acne, wounds, blisters, keloids, taking some medications like Accutane, antihypertensives, anticoagulants, systemic retinoids, topical retinoids, those undergoing cosmetic procedures, treatment with injecting fillers or ablative or non-ablative laser resurfacing, diabetes, collagen diseases and those who do not agree to participate in study were excluded. Results: Any change in the grading of scars after the end of treatment and follow-up period was noted. Efficacy and improvement of dermaroller treatment was assessed by Goodman and Baron’s global acne scarring system. Out of 18 patients (of total 28) with Goodman and Baron’s qualitative grade-4, 16 (88.90%) patients reduced to grade-1. 21 out of 28 patients achieved ‘excellent’ response. Adverse effects were limited to transient erythema and post inflammatory hyperpigmentation. Conclusions: Microneedling therapy seems to be simple, safe and efficacious for the management of atrophic facial acne scars.